Going local: a regional perspective on how trade affects labour markets and inequality - Rusticelli, Elena (OECD Economics Department Working Papers, 2018)
The increase of emerging market economies in international trade and rapid rise in global trade intensity over the past three decades has been accompanied by growing, regionally concentrated, discontent with trade in advanced OECD countries. One of the main concerns is the negative effects of growing import competition on employment. This paper focuses on manufacturing sector employment because of its high trade exposure and potential for wider spillovers. It finds that while trade appears to have only a minor association with manufacturing employment shares at the national level compared with technology, trade has an important role in regional labour market developments due to the geographical concentration of industrial activities. The "sticky" nature of manufacturing employment and sometimes inefficient inter-regional migration mean that trade shocks to local manufacturing can affect entire regional labour markets, leading to widening regional inequalities. Policies should, in particular, focus on boosting regional resilience to industry related shocks, whether they come from trade or technology by building local capacity, both in terms of people - more educated labour is more mobile across jobs - and innovation